Super charged [ultracapacitors]. - Zorpette, G.
The South Korean company, NessCap Co., is one of the about 10 makers of ultracapacitor, devices that can store so much charge that they are beginning to blur the functional distinction between the capacitor and the battery. They offer a unit rated at an impressive 5000 farads at 27 volts in a package a little bigger than a half-liter soda bottle and performs better in terms of energy and power density. In comparison with batteries, NessCap ultracapacitors can put out much more power for a given weight, can be charged in seconds rather than hours, and can function at more extreme temperatures. These ultracapacitors are superior to batteries in many respects and can certainly be used increasingly in hybrid-electric and fuel-cell cars.
Keywords: NessCap Co; South Korean company; Fuel-cell car; Hybrid-electric car; Power density; Ultracapacitor